Pelanserin: 3-[3-(4-phenylpiperazin-1-yl)propyl]quinazoline-2,4(1H,3H)-dione - Aguirre Hernández, Gerardo; Somanathan, Ratnasamy; Bernès, Sylvain (Wiley-Blackwell, 2014)
The title compound, C21H24N4O2, is a potent serotonin 5-HT2 and α1-adrenoceptor antagonist. The n-propyl chain links the quinazolinedione heterocycle and the phenylpiperazine group in which the benzene ring is equatorially located and the piperazine ring has the expected chair conformation. The dihedral angle between the planes of the benzene ring and the quinazolinedione ring system is 74.1 (1)°. In the crystal, molecules form centrosymmetric dimers through R22(8) hydrogen-bonded rings involving the amine and one carbonyl group of the quinazolinedione moiety. These dimers are extended into chains extending along the a-axis direction through expanded centrosymmetric cyclic C—H...O associations involving the second carbonyl group, giving R22(20) and R12(7) motifs.